The American Society of Colon and Rectal Surgeons and Surgical Education: What Does Your Society Do for You? - Trudel, Judith L. (Clinics in Colon and Rectal Surgery, 2012)
Since its inception in 1899, the American Society of Colon and Rectal Surgeons (ASCRS) has been actively providing support for the education of its members specializing in colon and rectal surgery, general surgeons, surgical residents, and medical students. With new developments in surgical education, the ASCRS continues to offer educational tools and activities tailored to meet acquisition of medical knowledge and technical skills in an ongoing fashion throughout surgeons' careers, foster high-quality patient care, and promote the integration of the core competencies of communication skills, professionalism, system-based practice and practice-based learning, and improvement in daily practice. These tools and activities are presented in this article.
Keywords: American Society of Colon and Rectal Surgery; ASCRS; professional society; career; membership